Hypogonadism in Benign Prostate Hyperplasia: A Cross Sectional Study: Hypogonadism in Benign Prostate Hyperplasia - Khan, Ismail; Aftab Younus, Malik; Shoaib, Mohammad; Haris, Muhammad; Ullah Wazir, Noman; Jehangir Khan, Muhammad; Haris, Sobia; Deeba, Farah (Pakistan Journal of Health Sciences, 2022)
Benign prostatic hyperplasia is a common health problem affecting men older than 50 years. It is estimated that 30 million men have benign prostatic hyperplasia related clinical features Objective: The objective of this study was to find out the relationship between hypogonadism in patients presenting with benign prostate hyperplasia at tertiary care center. Methods: A descriptive cross-sectional study conducted at Urology Department Lady Reading Hospital Peshawar for a period of one year from June 2019 to May 2020. A total of 361 patients with benign prostate hyperplasia were studied. The sampling technique was consecutive non probability sampling and WHO sample size calculator was used for sample size determination. Serum testosterone level was done all patients as per inclusion criteria. All the data was analyzed in SPSS version 20.0. Results: The mean age, height weight, BMI and testosterone level of qualitative variables were 56.42±10.05, 167.54±9.97, 64.96±12.92, 23.07±4.96 and 15.36±6.36 respectively. The testosterone level decreased with ageing in different age groups. 29.6% patients of our study were 50-59 years old. The hypertensive and diabetic patients with BPH were 31.3% and 22.4% respectively. Out of 361 patients 67 were hypo gonadal men making 18.6%. The hypogonadism had statistically significant mean values of serum testosterone level (p<0.001). Conclusions: This study concluded on the analytical findings that hypogonadism is significantly associated with benign prostate hyperplasia. The testosterone levels decrease with the increase of age and thus patients with low testosterones are more prone to develop benign prostate hyperplasia.